2007
DOI: 10.1007/s11606-007-0431-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Registry-generated Audit, Feedback, and Patient Reminder Intervention in an Internal Medicine Resident Clinic—A Randomized Trial

Abstract: BACKGROUND: Disease registries, audit and feedback, and clinical reminders have been reported to improve care processes. OBJECTIVE:To assess the effects of a registrygenerated audit, feedback, and patient reminder intervention on diabetes care. PARTICIPANTS: Seventy-eight categorical Internal Medicine residents caring for 483 diabetic patients participated. Residents randomized to the intervention (n=39) received instruction on diabetes registry use; quarterly performance audit, feedback, and written reports i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 21 publications
1
66
0
1
Order By: Relevance
“…Among the studies, 2 randomized controlled trials did not show a significant improvement in the levels of HbA 1c [24,25]. However, the first of these evaluated the effects of a registry-generated audit for diabetes, as well as feedback and patient reminder interventions on diabetes care, for 483 diabetic patients [24].…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies, 2 randomized controlled trials did not show a significant improvement in the levels of HbA 1c [24,25]. However, the first of these evaluated the effects of a registry-generated audit for diabetes, as well as feedback and patient reminder interventions on diabetes care, for 483 diabetic patients [24].…”
Section: Resultsmentioning
confidence: 99%
“…Other investigators have used these same outcome measures in cohort designs to study the effect of QI interventions and found no improvement in any of these 3 variables, 19 improvements in LDL and BP but not A1C, 20 or improvements in A1C and BP but not LDL. 21 Improving patient- or population-level clinical outcomes involves complex issues that rely on patient-, practice-, and system-level factors, and partial implementation of key drivers may have only small effects on outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an assessment of the validity of performance measures for coronary artery disease revealed that 15% to 81% of apparent quality failures in EHRs were actually audit failures,11 leading to questions about whether differences in performance reflect measurement or documentation errors as opposed to actual differences in quality of care 12. As residents wrestled with problems in clinical decision support13 14 and feedback systems,15–17 they discovered how to modify standardised codes,13 15 18 physician alerts and clinical reminders to aid in their own decision-making and improve their own quality of patient care.…”
Section: Discussionmentioning
confidence: 99%